Disproportionality analysis of fondaparinux associated adverse events based on the FDA adverse event reporting system - Fengjiao Kang; Yin Wang; Fengqun Cai; Liuyun Wu; LiZhu Han; Qinan Yin; Yuan Bian (PLoS ONE, 2026)
Fondaparinux is a widely used anticoagulant for treating venous thromboembolism and acute coronary syndrome by inhibiting factor Xa. However, it carries a risk of bleeding. This study analyzes its safety using the FDA Adverse Event Reporting System (FAERS) database to guide clinical use and future research. Data from 2004 Q1 to 2024 Q3 were examined using Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayesian Geometric Mean (EBGM) methods. Among 21,483,491 reports, 5,788 were related to fondaparinux, with 17,523 adverse events (AEs). The most affected systems were vascular (n = 2046) and blood/lymphatic (n = 1125). Abnormal coagulation factor X concentration, thrombosis with thrombocytopenia syndrome, and incision site hematoma had the strongest signals. AEs were more frequent in females and elderly patients, especially within the first month. Additional Preferred Term (PT)–level signals defined in MedDRA were observed, including heparin induced thrombocytopenia and eosinophilia. Heightened pharmacovigilance particularly in older adults may be warranted. This study enhances understanding of fondaparinux’s safety, providing insights for reducing risks and ensuring safer clinical application.